Foraging behaviour responses in the African giant land snail achatina achatina (2011)
The study was carried out to determine the conditioning procedure of tentacle lowering to determine foraging behavior responses in Achatina achatina. Snails were exposed to unripe fruit odour of pawpaw and pear as conditioned stimuli (CS), while they ingested carrot as a unconditioned stimulus (US). There were 4 treatments of 10 snails each replicated 3 times. During experimentation (conditioning), all snails ate carrot as US, but exposed to the odour of carrot in control treatment (T1); pawpaw in T2; pear in T3; pair of pawpaw and pear in T4 as CS respectively. Responses were data of posterior tentacle lowering. Results indicated T1 with highest tentacle lowering; T2 indicated an acquisition effect; T3 indicated latent inhibition effect; T4 indicated over shadowing effect between paired odour. The A. achatina demonstrated at least 7 days of odour memory retention. The immediate significance of this study is that snail farmers should feed their stock with a diet in which snails will develop habituation and hence optimal performance.